MAXIMIZING SPECIFIC CAPACITY OF NUTTY HARD CARBON: IMPACT OF TREATMENT CONDITIONS ON STRUCTURAL AND ELECTROCHEMICAL PROPERTIES - Bazybek, Nardana; Maratov, Maksat; Konarov, Aishuak (National Laboratory Astana, 2022)
Hard carbon (HC) has attracrted tremendous attention in sodium ion batteries (SIBs) as promising negative electrode material due to its low cost, environmental friendliness and stable cyling performance. However, due to the limited capacity and low initial columbic efficiency (ICE), the actual full cell application of HC faces significant obstacles. Therefore, preparation process was optimized to investigate the impact of the pre-treatment conditions and degree of graphitization on electrochemical performance and to resolve abovementioned problems.
Keywords: Type of access: Embargo; nutty hard carbon; sodium ion batteries